2000
DOI: 10.1007/pl00000626
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of HIV-1 resistance to nucleoside reverse transcriptase inhibitors (NRTIs)

Abstract: Nucleoside reverse transcriptase inhibitors (NRTIs), such as 3'-azido-3'-deoxythymidine, 2',3'-dideoxyinosine and 2',3'-dideoxy-3'-thiacytidine, are effective inhibitors of human immunodeficiency type 1 (HIV-1) replication. NRTIs are deoxynucleoside triphosphate analogs, but lack a free 3'-hydroxyl group. Once NRTIs are incorporated into the nascent viral DNA, in reactions catalyzed by HIV-1 reverse transcriptase (RT), further viral DNA synthesis is effectively terminated. NRTIs should therefore represent the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 65 publications
1
90
0
Order By: Relevance
“…Therefore, we cannot investigate its structural basis of resistant mutations by using MD simulations and free energy decompositions. To date, three biochemical mechanisms of NRTI drug resistance have been uncovered or proposed (3,17). These different resistance mechanisms seem to correlate with different sets of mutations in RT (17), but further biochemical investigations are needed to confirm which mechanism corresponds to which independent mutation set (SI Text).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we cannot investigate its structural basis of resistant mutations by using MD simulations and free energy decompositions. To date, three biochemical mechanisms of NRTI drug resistance have been uncovered or proposed (3,17). These different resistance mechanisms seem to correlate with different sets of mutations in RT (17), but further biochemical investigations are needed to confirm which mechanism corresponds to which independent mutation set (SI Text).…”
Section: Resultsmentioning
confidence: 99%
“…To date, three biochemical mechanisms of NRTI drug resistance have been uncovered or proposed (3,17). These different resistance mechanisms seem to correlate with different sets of mutations in RT (17), but further biochemical investigations are needed to confirm which mechanism corresponds to which independent mutation set (SI Text). Unlike NRTIs, NNRTIs bind to a hydrophobic pocket in RT close to the active site and their binding can block the catalytic activity of RT.…”
Section: Resultsmentioning
confidence: 99%
“…Two kinetically distinct mechanisms of HIV-1 resistance to NRTI have been described previously (6,30). One mechanism involves selective decreases in NRTI-TP versus normal dNTP incorporation during viral DNA synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…To better understand how p53 proteins orchestrate the cellular response to HIV infection, it may be essential to examine the location and extent of p53 binding to viral nucleic acids and to damaged cellular DNA and the interaction of p53 with other proteins in virus-infected cells. It was suggested that it is biologically beneficial for the virus to harbor a low-fidelity RT for purposes such as allowing the virus to evade the immune system of the host, as well as drugs aimed against the virus (Mansky and Temin, 1995;Sluis-Cremer et al, 2000). Hence, a question arises regarding whether the presence of exonuclease activity in cytoplasm is of interest for the virus.…”
Section: Discussionmentioning
confidence: 99%